Penicillin Susceptibility and Macrolide-Lincosamide-Streptogramin B Resistance in Group B Streptococcus Isolates from a Canadian Hospital - Kevin Sherman; Sue Whitehead; Edith Blondel-Hill; Ken Wagner; Naowarat Cheeptham (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Intrapartum antibiotic prophylaxis (IAP) is recommended for pregnant women who test positive for group B Streptococcus (GBS) in their genitourinary tract to prevent GBS-induced neonatal sepsis. Penicillin G is used as the primary antibiotic, and clindamycin or erythromycin as the secondary, if allergies exist. Decreased susceptibility to penicillin G has occasionally been reported; however, clindamycin and erythromycin resistance is on the rise and is causing concern over the use of clindamycin and erythromycin IAP.